2020
DOI: 10.1186/s40494-020-0349-8
|View full text |Cite
|
Sign up to set email alerts
|

FTIR surface analysis for conservation

Abstract: Several FTIR techniques are surface-sensitive. This sensitivity can be utilized to help with a wide range conservation issues. Examples from object degradation studies, conservation materials performance assessment and monitoring are presented. These are used to discuss the issues, advantages and information that can be drawn from studies. Glass degradation was quantified on the surfaces of cover glasses from important Nineteenth century daguerreotypes using Germanium attenuated total reflectance. The very lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
0
19
1
Order By: Relevance
“…Acrylic lacquers are coupled with a sacrificial wax topcoat that is renewed yearly in the case of Morse. Since 2003, two types of cyclically renewable wax topcoats have been used by CPC's conservators: (1) Boston Polish ™ , also known as "butchers" paste wax, a carnauba-based wax, in use from 2003 to 2006; (2) Renaissance microcrystalline wax ™ , a mixture of Cosmoloid H80 and BASF A wax [22,23], used from 2007 to In terms of coloring, verbal accounts and visual observation suggested that the Morse sculpture might have been coated with pitch at some early stage, although there are no written records of this intervention. The color of organic coatings in bronze sculptures is also sometimes obtained through the addition of bitumen, which might lend the coating a dark or brown hue [24].…”
Section: Analysis Of Organic Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acrylic lacquers are coupled with a sacrificial wax topcoat that is renewed yearly in the case of Morse. Since 2003, two types of cyclically renewable wax topcoats have been used by CPC's conservators: (1) Boston Polish ™ , also known as "butchers" paste wax, a carnauba-based wax, in use from 2003 to 2006; (2) Renaissance microcrystalline wax ™ , a mixture of Cosmoloid H80 and BASF A wax [22,23], used from 2007 to In terms of coloring, verbal accounts and visual observation suggested that the Morse sculpture might have been coated with pitch at some early stage, although there are no written records of this intervention. The color of organic coatings in bronze sculptures is also sometimes obtained through the addition of bitumen, which might lend the coating a dark or brown hue [24].…”
Section: Analysis Of Organic Coatingsmentioning
confidence: 99%
“…It seems plausible that the water enriched with these ions could become aerosolized by the constant traffic whisking by and deposited onto the bronze. Thickett and coauthors [22,23] have demonstrated that water may be retained at the interface between the superficial layer of Renaissance wax and the coating underneath, further enhancing the corrosive attack. On ferrous metals, like steel, the prolonged exposure to this trapped moisture after the protective period of the coating might increase the rate of corrosion.…”
Section: Analysis Of Corrosion Productsmentioning
confidence: 99%
“…Acrylic lacquers are coupled with a sacrificial wax topcoat that is renewed yearly in the case of Morse. Since 2003, two types of cyclically renewable wax topcoats have been used by CPC's conservators: 1) Boston Polish™, also known as "butchers" paste wax, a carnauba-based wax, in use from 2003 to 2006; 2) Renaissance microcrystalline wax™, a mixture of Cosmoloid H80 and BASF A wax [22][23], used from 2007 to date for protecting outdoor bronze sculptures in Central Park.…”
Section: Analysis Of Organic Coatingsmentioning
confidence: 99%
“…Acrylic lacquers are coupled with a sacri cial wax topcoat that is renewed yearly in the case of Morse. Since 2003, two types of cyclically renewable wax topcoats have been used by CPC's conservators: 1) Boston Polish™, also known as "butchers" paste wax, a carnauba-based wax, in use from 2003 to 2006; 2) Renaissance microcrystalline wax™, a mixture of Cosmoloid H80 and BASF A wax [22][23], used from 2007 to date for protecting outdoor bronze sculptures in Central Park.…”
Section: Analysis Of Organic Coatingsmentioning
confidence: 99%
“…It seems plausible that the water enriched with these ions could become aerosolized by the constant tra c whisking by and deposited onto the bronze. Thickett and coauthors [22][23] have demonstrated that water may be retained at the interface between the super cial layer of Renaissance wax and the coating underneath, further enhancing the corrosive attack. On ferrous metals, like steel, the prolonged exposure to this trapped moisture after the protective period of the coating might increase the rate of corrosion.…”
Section: Analysis Of Corrosion Productsmentioning
confidence: 99%